Hypoxia triggers IFN-I production in muscle: Implications in dermatomyositis - Noemí De Luna (Nature Portfolio, 2017)
Abstract Dermatomyositis is an inflammatory myopathy characterized by symmetrical proximal muscle weakness and skin changes. Muscle biopsy hallmarks include perifascicular atrophy, loss of intramuscular capillaries, perivascular and perimysial inflammation and the overexpression of IFN-inducible genes. Among them, the retinoic-acid inducible gene 1 (RIG-I) is specifically overexpressed in perifascicular areas of dermatomyositis muscle. The aim of this work was to study if RIG-I expression may be modulated by hypoxia using an in vitro approach. We identified putative hypoxia response elements (HRE) in RIG-I regulatory regions and luciferase assays confirmed that RIG-I is a new HIF-inducible gene. We observed an increase expression of RIG-I both by Real time PCR and Western blot in hypoxic conditions in human muscle cells. Cell transfection with a constitutive RIG-I expression vector increased levels of phospho-IRF-3, indicating that RIG-I promotes binding of transcription factors to the enhancer sequence of IFN. Moreover, release of IFN-β was observed in hypoxic conditions. Finally, HIF-1α overexpression was confirmed in the muscle biopsies and in some RIG-I positive perifascicular muscle fibres but not in controls. Our results indicate that hypoxia triggers the production of IFN-I in vitro, and may contribute to the pathogenesis of DM together with other inflammatory factors.